In-vitro Antibiotic Activity of Dry Ginger Root Extract against Potential enteropathogenic Bacteria isolated from two Weeks old Broiler Chickens - V. D., Zige; R. T. S., Ofongo (International Journal of Environment, Agriculture and Biotechnology, 2019)
Zoonotic enteropathogenic bacteria of poultry origin is a source of concern to public health. Dependent on various factors, poultry birds may not necessarily fall prey to sub-clinical infections induced by zoonotic enteropathogenic bacteria. A preliminary study was carried out to determine antibacterial activity of dry ginger root (Zingerbain officinalle) extract on Salmonella sp and Escherichia coli isolated from the crop, ileum and caecum of two weeks broiler birds. The in-vitro antibacterial activity was determined by agar disc diffusion method on pre-prepared sensitivity test agar with respective cells inoculated and incubated after 24 hours. Zone of inhibition measured in millimeters after observation gave an inhibition zone of 11.8 ± 2.2, 15.0 ± 2.4, 15.0 ± 2.4 and 14.0 ± 2.9, 13.0 ± 2.3, 8.2 ± 2.6, 15.0 ± 2.2, against Salmonella and E coli respectively, isolated from crop, ileum and caecum. The highest zone of inhibition was observed in the ileum (15.0 ± 2.4) for Salmonella and caecum (15.0 ± 2.2) for E coli. The least was observed in crop (11.8 ± 2.2) and ileum (8.2 ± 2.6) respectively. It is evident that dry ginger root extract has anti-bacterial activity against Salmonella sp and E. coli isolated from the gut of two weeks old broiler birds.